1995
DOI: 10.1002/jnr.490410305
|View full text |Cite
|
Sign up to set email alerts
|

Glia‐to‐axon communication: Enrichment of glial proteins transferred to the squid giant axon

Abstract: The transfer of newly synthesized proteins from the glial sheath into the axon is a well-documented process for the squid giant axon. In this study, we used a novel approach to separate the transferred glial proteins (TGPs) from the endogenous axoplasmic proteins of the squid giant axon. Axoplasm, containing radiolabelled TGPs, was extruded as a cylinder and immersed in an intracellular buffer. After 1-30 min, the TGPs were enriched in the intracellular buffer, because they were eluted from the axoplasm into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…In later studies, the synthesis of axoplasmic proteins by the isolated giant axon of Loligo pealii was confirmed (3), and the question of their cellular localization was addressed (104,200,201,277,303). At the end of a series of experiments, the conclusion was reached that the axoplasmic proteins synthesized by the isolated giant axon were entirely derived from periaxonal glia (the glia-neuron protein transfer hypothesis).…”
Section: The Squid Giant Axonmentioning
confidence: 99%
See 1 more Smart Citation
“…In later studies, the synthesis of axoplasmic proteins by the isolated giant axon of Loligo pealii was confirmed (3), and the question of their cellular localization was addressed (104,200,201,277,303). At the end of a series of experiments, the conclusion was reached that the axoplasmic proteins synthesized by the isolated giant axon were entirely derived from periaxonal glia (the glia-neuron protein transfer hypothesis).…”
Section: The Squid Giant Axonmentioning
confidence: 99%
“…157). While the latter data were severely criticized (193), and the possibility of glia-to-neuron transfer of RNA was largely forgotten, the concept of the glia-neuron unit was revived in studies of the local synthesis of proteins in isolated giant axons of crayfish (30,147) and squid (104,200,201,277,303). The squid data were taken to support the idea that locally synthesized axonal proteins exclusively derive from periaxonal glia, although later experiments demonstrated this view to be incorrect (see sects.…”
Section: The Local System Of Gene Expression In Axons and Nerve Tmentioning
confidence: 99%
“…A variety of evidence, mainly from experiments on squid giant axons, demonstrated that the axoplasmic RNAs are partially transferred from extra-axonal glia (Edstrom et al 1969;Gainer et al 1977;Lasek et al 1977;Cutillo et al 1983;Rapallino et al 1988;Buchheit & Tytell, 1992). However, the glial-axonal transfer of proteins did not appear to involve the conventional secretory exocytic and endocytic pathways (Sheller et al 1995).…”
Section: Polyribosomal Clusters In the First Internodementioning
confidence: 99%
“…The transfer of HSPs and other proteins may involve nonconventional secretion in which cytosolic proteins that lack the signal sequences required for Golgimediated secretion are translocated across the glial plasmalemma (Hightower and Guidon, 1989;Mignatti et al, 1992;Sheller et al, 1995) and then across the axolemma (Sheller et al, 1995). Because HSPs are essential molecular chaperons that assist other proteins in crossing cellular membranes, this intercellular transfer may be aided by induced members of the HSP 70 family that are secreted by the glia in response to a stress or by some constitutive members of the HSP 70 family that are present normally in the cytoplasm of the axon and/or glia.…”
Section: Proposed Mechanism Of Glia-to-axon Transfermentioning
confidence: 99%